Development and validation of a nutrition education module on free sugar for individuals with metabolic syndrome: My 3S (Smart Sugar Study) - Chiang, Wan Ling; Mohd Yusof, Barakatun Nisak; Azlan, Azrina; Ismail, Irmi Zarina; Abu Zaid, Zalina (Faculty of Medicine, 2026)
Metabolic syndrome (MetS) is a measure of an individual’s risk of developing cardiovascular disease. This paper describes the development and validation of a nutrition education module, The My 3S (Smart Sugar Study) that focused on free sugar. Methodology: The My 3S have three phases: Phase 1 Needs assessment, Phase 2 Development and validation of nutrition education module, and Phase 3 Feasibility study. Phase 1 Needs assessment, which is a cross- sectional study was conducted using surveys on dietary free sugar of general population (n=209) and individuals with MetS (n=39), and clinical observation of dietetic consultation (n=20). The inclusion criteria included Malaysian; 30-65 years old; able to communicate in Malay or English; presence with MetS. The module development involved five experts in nutrition, dietetics, and medicine. The content validity was conducted using a content validity index (CVI) among five expert panels who were health care experts. And the face validity involved 32 target audiences and five expert panels. Result: The free sugar of individuals with MetS was 18.6 (9.09) % of total energy intake and the dietetic consultation did not include daily free sugar allowance. The developed module showed good content validity (CVI = 1.0) and face validity (average score of 78.3% to 91.7% from the expert panels and 96.9% to 100.0% from the target audiences). Conclusion: Individuals with MetS consumed high free sugar and there is lack of nutrition education module on free sugar for them. The newly developed nutrition education module can be used to educate individuals with MetS and high free sugar.